Dual‐band microstrip‐fed bow‐tie antenna for GPS and WLAN application. Issue 9 (September 2014) - Liu, Hai‐Wen; Qin, Feng; Lei, Jiu‐Huai; Wen, Pin; Ren, Bao‐Ping; Xiao, Xiang
ABSTRACT A novel microstrip‐fed bow‐tie antenna for the global positioning system (GPS) and wireless local area network (WLAN) applications is presented in this letter. The proposed antenna consists of two pairs of printed bow‐tie patches with different dimensions, which can generate dual‐band characteristics independently. Based on this design concept, a prototype of the dual‐band antenna is fabricated and measured. The simulated and measured reflection coefficients, together with the radiation patterns, are presented and compared. Measurements show that the 10‐dB impedance bandwidth of the proposed dual‐band bow‐tie antenna is about 670 MHz (1.22–1.89 GHz) and 1130 MHz (5.24–6.37 GHz), which can cover both the GPS and WLAN bands. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2088–2091, 2014